2020
DOI: 10.1186/s12985-020-01390-2
|View full text |Cite
|
Sign up to set email alerts
|

Association of human cytomegalovirus (HCMV) neutralizing antibodies with antibodies to the HCMV glycoprotein complexes

Abstract: Background: Human cytomegalovirus (HCMV) causes asymptomatic infections, but also causes congenital infections when women were infected with HCMV during pregnancy, and life-threatening diseases in immunocompromised patients. To better understand the mechanism of the neutralization activity against HCMV, the association of HCMV NT antibody titers was assessed with the antibody titers against each glycoprotein complex (gc) of HCMV. Methods: Sera collected from 78 healthy adult volunteers were used. HCMV Merlin s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 52 publications
1
5
0
Order By: Relevance
“…Transplacental transmission of anti-gM/gN antibodies to late preterm and full term infants was significantly lower than that of anti-gB antibodies. Human anti-gM/gN antibodies have been shown to neutralize CMV infection in-vitro and in a murine model but, similar to our findings, a recent study of non-pregnant CMV seropositive adults showed that anti-gM/gN titers did not correlate with in-vitro serum neutralizing activity ( 25 , 26 , 28 ). The reasons for the discrepancy between in-vitro and animal model data compared to clinical serologic responses are unclear, and it is unknown whether increasing human anti-gM/gN titers could improve serum CMV-neutralizing potential.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Transplacental transmission of anti-gM/gN antibodies to late preterm and full term infants was significantly lower than that of anti-gB antibodies. Human anti-gM/gN antibodies have been shown to neutralize CMV infection in-vitro and in a murine model but, similar to our findings, a recent study of non-pregnant CMV seropositive adults showed that anti-gM/gN titers did not correlate with in-vitro serum neutralizing activity ( 25 , 26 , 28 ). The reasons for the discrepancy between in-vitro and animal model data compared to clinical serologic responses are unclear, and it is unknown whether increasing human anti-gM/gN titers could improve serum CMV-neutralizing potential.…”
Section: Discussionsupporting
confidence: 85%
“…Glycoprotein M is the most abundant component of the viral proteome and is complexed to glycoprotein N, which exhibits sequence variation and glycosylation consistent with immune evasion functions (19)(20)(21)(22). This complex elicits antibodies with in vitro neutralizing capacity that are detectable among seropositive adults and in CMV hyperimmune globulin (19,(23)(24)(25)(26)(27). In mice, co-immunization with DNA vaccines encoding murine CMV (MCMV) gM and gN provided mice with complete protection against lethal MCMV challenge (28).…”
Section: Introductionmentioning
confidence: 99%
“…Such LLPC and their secreted antibodies represent the first line of humoral defense against re-infection with pathogens such as seasonal influenza [12], Ebola [13], Dengue [14] and most recently the SARS-CoV-2 virus [15]. Moreover, pre-existing antibodies also serve to counter reactivation and subsequent dissemination of latent viral infections such as Epstein-Barr virus (EBV) [16] and human cytomegalovirus (HCMV) [17,18]. In this context, elevated levels of serum antibody reactivity serve as a reliable indicator of antigenic exposure.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, HCMV IgM was not analyzed in this study. HCMV strain- or glycoprotein complex-specific neutralizing antibodies modulate HCMV infection by preventing binding of HCMV to target cells ( Martins et al., 2019 ; Shibamura et al., 2020 ). However, the method is complicated and has yet to be standardized.…”
Section: Discussionmentioning
confidence: 99%